Addressing racism in the healthcare encounter: The role of clinical ethics consultants. (7th February 2022) - MacDuffie, Katherine E.; Patneaude, Arika; Bell, Shaquita; Adiele, Alicia; Makhija, Neena; Wilfond, Benjamin; Opel, Douglas
Abstract: Justice is a core principle in bioethics, and a fair opportunity to achieve health is central to this principle. Racism and other forms of prejudice, discrimination, or bias directed against people on the basis of their membership in a particular racial or ethnic group are known contributors to health inequity, defined as unjust differences in health or access to care. Though hospital‐based ethics committees and consultation services routinely address issues of justice that arise in the course of patient care, there is variability in whether and how racism and other causes of health inequities are addressed. In this paper, we describe a novel structure and process for addressing health equity within clinical ethics consultation. In addition, we discuss the barriers and challenges to its success, many of which are rooted in the identities, norms and assumptions that underlie traditional clinical ethics consultation. We offer pragmatic recommendations and conclude with unresolved questions that remain as we work to adapt the structure of a clinical ethics consultation service to improve attention to issues of health equity and promote anti‐racism in patient care and institutional policy.